Radical Prostatectomy Practice in England - Hanchanale, Vishwanath S; McCabe, John E; Javlé, Pradip (Urology Journal, 2010)
<!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE FA <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Purpose: As there is paucity of data on radical prostatectomy (RP) as a primary treatment for patients with localized prostate cancer, we analyzed the trends in the RP practice in England. Materials and Methods: This study was carried out on 14 300 patients who underwent RP for carcinoma of the prostate. Database was prepared from hospital episode statistics of the Department of Health in England. National trends in RP practice were summarized as well as volume outcome analysis. Results: Annual number of RPs exponentially increased from 972 (1998 to 1999) to 3092 (2004 to 2005). Laparoscopic RPs increased from 2 to 257 over the study period. Median waiting duration increased by more than 10 days (13 days). Significant decrease in median length of hospital stay from 8 (range, 7 to 10) days to 6 (range, 5 to 8) days was observed (P < .001). More than 90% mortality was seen in patients of ≥ 60 years of age. Significant inverse correlation was found between the hospital volume (Odds Ratio: 0.40) and in-hospital mortality rate following RP. High volume surgeons (≥ 16) and high volume hospitals (≥ 26) had significantly lower mortality (Odds Ratio: 0.32) and shorter in-hospital stay in comparison to low volume surgeons and hospitals. Conclusion: There is an exponential increase in the number of RPs with an increasing trend towards laparoscopic RP in England. This study showed a significant inverse correlation between rovider volume (hospital and surgeon) and outcome (in-hospital mortality and hospital stay) for RP in England; thus, supporting the recommendations for centralization of care for complex radical procedures, including RP.